Improvement of covered wagons of the “East-West” type by sectioning with a partition - Fomin, Oleksij; Lovska, Alyona; Klymash, Andriy; Keremet, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2021)
The dynamic loading and strength of the frame of the “East-West” type covered wagon were determined. To increase the efficiency of operation of covered wagons in international traffic, it is proposed to improve their frames. This improvement consists in using a sectional partition in the body in order to divide it into two separate sections. This allows the transportation of different goods in one wagon, and therefore decreasing empty mileage. The longitudinal loading of the covered wagon frame was determined. The case of shunting impact was considered. The studies were carried out in a flat coordinate system. The loading mode of the frame of the covered wagon in the empty and loaded states was considered. The acceleration acting on the covered wagon frame in the loaded state was 0.37g, empty – 0.42g, which does not exceed the standard values. The wagon motion is rated “excellent”. The main strength indicators of the covered wagon frame were determined. The calculation was made by the finite element method. It was found that the maximum equivalent stresses are concentrated in the area of interaction of the center sill with the bolster beam and amounted to 340 MPa, which is lower than the yield stress of the material. Maximum displacements occur in the middle of the frame beams and are about 12 mm. The natural vibration frequencies of the covered wagon frame were calculated. The research will help to increase the efficiency of using covered wagons in international traffic. Also, the research results can be useful developments in the creation of innovative rolling stock structures